Shah Wali Allah al-Dihlawi's ideas on the study of modern Malay literature - Narmi, Akalily; Abdul Rani, Mohd. Zariat; Kamarudin, Kamariah; Hajimaming @ Toklubok, Pabiyah; Roslan, Samsilah (Human Resource Management Academic Research Society, 2021)
Shah Waliyullah al-Dihlawi is a renowned Muslim scholar who lived in the 17th century and has contributed his profound ideas in the Islamic scientific tradition. In Malaysia, al-Dihlawi's ideas have influenced the field of Islamic studies in the early 20th century. In the latest development, al-Dihlawi’s ideas have also influenced the field of Malay literature. Mohd. Affandi Hassan has made extensive reference on al-Dihlawi’s explication on taklif in his literary notion namely “Persuratan Baru” (translated into English as “Genuine Literature”). The concept of taklif in “Persuratan Baru” has also been presented as an analytical tool for literary studies. This study aims to discuss the application of taklif in the study of modern Malay literature, and summarizes the major findings resulting from its application. This study utilises qualitative research method, particularly library research and textual analysis. The findings show that the application of taklif has allowed academic studies to unravel the confusion of values in the modern Malay literary works. In this context, al-Dihlawi's ideas are considered as a significant contribution to the field of modern Malay literature.